2020
DOI: 10.1073/pnas.1820132117
|View full text |Cite
|
Sign up to set email alerts
|

A plant DNA virus replicates in the salivary glands of its insect vector via recruitment of host DNA synthesis machinery

Abstract: Whereas most of the arthropod-borne animal viruses replicate in their vectors, this is less common for plant viruses. So far, only some plant RNA viruses have been demonstrated to replicate in insect vectors and plant hosts. How plant viruses evolved to replicate in the animal kingdom remains largely unknown. Geminiviruses comprise a large family of plant-infecting, single-stranded DNA viruses that cause serious crop losses worldwide. Here, we report evidence and insight into the replication of the gem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 52 publications
(105 reference statements)
0
70
0
1
Order By: Relevance
“…In addition, circumstantial evidence of TYLCV replication is provided by the successful transovarial transmission of the virus from one generation to the next of the whitefly vector ( 11 14 ). Equally important, case studies also showed that both replication and transovarial transmission of TYLCV in whiteflies may be conditional and intermittent ( 13 , 14 ), and the replication of TYLCV occurs mainly in the salivary glands of the whitefly vector ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, circumstantial evidence of TYLCV replication is provided by the successful transovarial transmission of the virus from one generation to the next of the whitefly vector ( 11 14 ). Equally important, case studies also showed that both replication and transovarial transmission of TYLCV in whiteflies may be conditional and intermittent ( 13 , 14 ), and the replication of TYLCV occurs mainly in the salivary glands of the whitefly vector ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is tempting to speculate whether it can alter the insect cell cycle and induce an endoreplication cycle as in plants or has evolved alternate strategies in the insect. Not all begomoviruses appear to replicate in the whitefly [37], and hence additional efforts are needed to understand why only certain virus species replicate within the insect. The continuous virus replication might not be beneficial to the viruses, because this can induce insect autophagy and antimicrobial peptide production leading to virion destruction and the inhibition of prolonged virus replication [38].…”
Section: The Voyage Of Virus Inside the Insect Vectormentioning
confidence: 99%
“…The continuous virus replication might not be beneficial to the viruses, because this can induce insect autophagy and antimicrobial peptide production leading to virion destruction and the inhibition of prolonged virus replication [38]. The active viral gene transcription of some begomoviruses can occur within the insect [37][38][39]. Strikingly, an insect transcription factor promotes viral gene transcription by binding to a CACGTG motif at the IR of a begomovirus [40].…”
Section: The Voyage Of Virus Inside the Insect Vectormentioning
confidence: 99%
“…Taken together, these results suggest that DNA polymerase α is essential for the initial synthesis of the viral complementary strand, and therefore for the generation of the dsDNA replicative intermediate, while DNA polymerase δ, alone or in combination with α, is required for the following RCR. Interestingly, TYLCV has been recently proven to replicate in the insect vector in a DNA polymerase δ-dependent manner (He et al, 2020), which raises the idea that the mechanisms replicating geminiviruses might be conserved between the animal and plant kingdoms.…”
Section: Main Textmentioning
confidence: 99%